Identification of a Novel Pattern Recognition Receptor DM9 Domain Containing Protein 4 as a Marker for Pro-Hemocyte of Pacific Oyster Crassostrea gigas - Jia, Zhihao; Jiang, Shuai; Wang, Mengqiang; Wang, Xiudan; Liu, Yu; Lv, Zhao; Song, Xiaorui; Li, Yiqun; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2021)
DM9 refers to an uncharacterized protein domain that is originally discovered in Drosophila melanogaster. Two proteins with DM9 repeats have been recently identified from Pacific oyster Crassostrea gigas as mannose-specific binding pattern-recognition receptors (PRRs). In the present study, a novel member of DM9 domain containing protein (designated as CgDM9CP-4) was identified from C. gigas. CgDM9CP-4, about 16 kDa with only two tandem DM9 domains, was highly enriched in hemocytes and gill. The transcripts level of CgDM9CP-4 in circulating hemocytes were decreased after LPS, PGN and Vibrio splendidus stimulations. The recombinant protein of CgDM9CP-4 (rCgDM9CP-4) displayed a broad binding spectrum towards various pathogen-associated molecular patterns (PAMPs) (LPS, PGN, β-glucan and Mannose) and microorganisms (Staphylococcus aureus, Micrococcus luteus, V. splendidus, V. anguillarum, Escherichia coli, Pichia pastoris and Yarrowia lipolytica). CgDM9CP-4 was mostly expressed in gill and some of the hemocytes. Flow cytometry analysis demonstrated that the CgDM9CP-4-positive hemocytes accounted for 7.3% of the total hemocytes, and they were small in size and less in granularity. CgDM9CP-4 was highly expressed in non-phagocytes ( 82% of total hemocytes). The reactive oxygen species (ROS) and the expression levels of cytokines in CgDM9CP-4-positive hemocytes were much lower than that in CgDM9CP-4-negative hemocytes. The mRNA expression level of CgDM9CP-4 in hemocytes was decreased after RNAi of hematopoietic-related factors (CgGATA, CgRunt, CgSCL, and CgNotch). In addition, CgDM9CP-4-positive cells were found to be much more abundant in hemocytes from gill than that from hemolymph, with most of them located in the gill filament. All these results suggested that CgDM9CP-4 was a novel member of PRR that expressed in undifferentiated pro-hemocytes to mediate immune recognition of pathogens.